Change management steps among SMEs - Filep, Roland (Marketing & Menedzsment, 2024)
THE AIMS OF THE PAPER The primary objective of the analysis was to create a detailed, multi-step model through the comparison of change management models found in the literature, encompassing all aspects of the change process during organizational transformation. One of the sub-goals was to test the developed model among SMEs through primary research, which also explored whether respondents considered increasing the frequency of any particular step to be important compared to current practices. METHODOLOGY To fulfill these goals, I used a t-test in addition to literature analysis and descriptive statistics. I worked with a sample size of 100 from the leaders of organizations based in Hungary. The sample includes organizations from manufacturing, services, and trade sectors in almost equal proportions. MOST IMPORTANT RESULTS The paper creates the broadest model containing the most steps by identifying, comparing and analyzing the steps included in change management models. It has been proven that the Yukl model (which is the broadest model with the largest number of steps available) should be supplemented with a starting and a closing step. RECOMMENDATIONS Based on the reviewed literature, the subject of my investigation, i.e., the comparison of the level of steps currently used and considered desirable, has not yet been tested in the literature. This seems to be a promising area of research, as such a study could offer valuable insights into whether leaders are aware of the necessary steps or which actions need greater emphasis to achieve success. These insights could prove particularly beneficial for SME leaders in ensuring effective change management. Raising awareness among SME leaders about the importance of planned change is strongly recommended.